Advances in Imaging in Evaluating the Efficacy of Neoadjuvant Chemotherapy for Breast Cancer - Kong, Xianshu; Zhang, Qian; Wu, Xuemei; Zou, Tianning; Duan, Jiajun; Song, Shujie; Nie, Jianyun; Tao, Chu; Tang, Mi; Wang, Maohua; Zou, Jieya; Xie, Yu; et al. (Frontiers in Oncology, 2022)
Neoadjuvant chemotherapy (NAC) is increasingly widely used in breast cancer treatment, and accurate evaluation of its response provides essential information for treatment and prognosis. Thus, the imaging tools used to quantify the disease response are critical in evaluating and managing patients treated with NAC. We discussed the recent progress, advantages, and disadvantages of common imaging methods in assessing the efficacy of NAC for breast cancer.